The Development of Traditional Banjar Ethnic Food Module in Johor - Abdul Rahman, Abdul Wafi; Md Sahak, Adibah Aishah; Aliah, Shamimi; Raden Ismail, Raden Mohd Farhan Helmy; Rohiat, Mohd Akmal (Research and Innovation in Technical and Vocational Education and Training, 2022)
The development of the module has helped educators and students throughout the teaching and learning process and has been a source of reference for both faculty and students. The main problem is that there is no complete source of reference for the traditional Banjar Ethnic Food Module in Johor for those who need this module. This study uses quantitative methods in which the data will be evaluated based on the average percentage of expert evaluators by using the expert evaluation form by 5 specialists consisting of lectures in the Hospitality field at the selected study Center in Malaysia. The result has shown that the level of suitability in terms of content, format, clarity, and design of the module is at a high level which is suitable for development and use by educators and students. In conclusion, the development of the learning module for the subject of Malay Cuisine is suitable for development based on expert feedback, and the development of this module will help educators as well as students during the study session as well as a source of reference.